15. STRESS AND COPING STRESS STRATEGIES AMONG 10TH GRADE ETHNIC BOARDING STUDENTS OF VIET BAC HIGHLAND HIGH SCHOOL FROM 2023 TO 2024 (Tạp chí Y học Cộng đồng, 2024)
Objectives: Describe ways to cope with stress in 10th grade boarding ethnic students at Viet Bac Highlands High School from 2023 to 2024.Materials and Methods: Cross-sectional descriptive research design using a set of survey questions on 262 10th grade students at Viet Bac Highlands High School for the 2023-2024 school year from February 2024 to the end of March 2024.Results: The most frequently used Problem-Focused Coping (X̅ = 2.7 ± 0.91), followed by Emotion-Focused Coping (X̅ = 2.49 ± 0.99) and the least Avoidant Coping (X̅ = 2.23 ± 0.99). The most frequently used response is “Acceptance”, at least “Substance use”. Students having chronic disease tend to choose "Self-blame" and " Behavioral disengagement “. Meanwhile, students who do not have chronic disease tend to " Acceptance " and “Active coping” more when faced with stress.Conclusions: Among the 3 forms of coping: Focusing on emotions, focusing on problems and abnormal coping methods (a total of 14 coping methods), "Problem focusing" is the most popular form. used most often. Considering a total of 14 coping methods: the "Accepting the problem" method is the most used. Students with chronic diseases: this subject uses 5 methods: "Religion", "Denial", "Stimulant use", "Lack of engagement behavior", "Self-blame". “self” more than students without chronic diseases and the difference is statistically significant.
Keywords: Coping strategy; 10th grade ethnic boarding student